2001
DOI: 10.1080/003655901753224387
|View full text |Cite
|
Sign up to set email alerts
|

Chemolysis of Struvite Stones by Acidification of Artificial Urine - An in vitro Study

Abstract: The acidification of urine accelerated the dissolution rate of struvite stones in vitro. Considering in vivo conditions the intake of 1,500-3,000 mg L-methionine may lead to a sufficient acidification for a good dissolution of struvite stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To deal with the latter effect, P recovery from waste streams with struvite precipitation is performed within an optimal pH range, generally between 8 and 10 (Liu et al, 2013). The average pH of the runoff water (pH 6.9) in the runoff experiment is only slightly below this range, proving relative stable conditions for a solid struvite phase, whereas more acidic conditions would increase the dissolution rate of the struvite granules ( Jacobs et al, 2001). Since the release of P from struvite to the surface water is related to its dissolution, it is to be expected that this release continues as long as undissolved material is available.…”
Section: Discussionmentioning
confidence: 99%
“…To deal with the latter effect, P recovery from waste streams with struvite precipitation is performed within an optimal pH range, generally between 8 and 10 (Liu et al, 2013). The average pH of the runoff water (pH 6.9) in the runoff experiment is only slightly below this range, proving relative stable conditions for a solid struvite phase, whereas more acidic conditions would increase the dissolution rate of the struvite granules ( Jacobs et al, 2001). Since the release of P from struvite to the surface water is related to its dissolution, it is to be expected that this release continues as long as undissolved material is available.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies evaluating the effect of calcium sulphate supplementation in dogs (3.17 g S/kg of diet, Janczikowski et al, 2008) and cats (2.56 g S/kg of diet, Halfen et al, 2018) showed only a small and not significant urinary pH acidification effect, this result might have been due to a low intake of calcium sulphate, which was probably insufficient to produce significant urinary acidification. Multiple studies verified the effectiveness of L-methionine/DL-methionine as a urinary acidifier in humans, cats and dogs (Funaba et al, 2001;Halfen et al, 2018;Hickey et al, 2015;Jacobs et al, 2001;Siener et al, 2016;).…”
Section: Discussionmentioning
confidence: 92%
“…A couple of studies evaluating the effect of calcium sulphate supplementation in dogs (3.17 g S/kg of diet, Janczikowski et al., 2008) and cats (2.56 g S/kg of diet, Halfen et al., 2018) showed only a small and not significant urinary pH acidification effect, this result might have been due to a low intake of calcium sulphate, which was probably insufficient to produce significant urinary acidification. Multiple studies verified the effectiveness of l ‐methionine/ dl ‐methionine as a urinary acidifier in humans, cats and dogs (Funaba et al., 2001; Halfen et al., 2018; Hickey et al., 2015; Jacobs et al., 2001; Siener et al., 2016;). In the present study, urinary pH oscillated between 5.30 and 6.16 when the dogs were fed the Urinary S/O diet, and although the present study was not designed to determine the impact of any specific nutrient on urinary pH, it is expected that the methionine content of this diet had a major influence on its acidifying effect.…”
Section: Discussionmentioning
confidence: 94%
“…A goal for controlling phosphatic urolithiasis is to, at least periodically, reduce the urine pH below 6.5, the target pH for dissolution. 26,27 This can be done in a variety of ways, including reducing the DCAD of the total diet to 0 mg/kg using chloride salts. 28,29 D, L methionine at a dosage of 200mg/kg orally daily has been shown to effectively reduce urine pH.…”
Section: Preventive Managementmentioning
confidence: 99%